Microcalorimetric Measurements of the Solvent Contribution to the Entropy Changes upon Electrochemical Lithium Bulk Deposition1. Issue 50 (24th October 2013) - Schmid, Matthias J.; Bickel, Katrin R.; Novák, Petr; Schuster, Rolf
<x xml:space="preserve">Abstract</x> A strongly positive entropy of reaction for the bulk deposition of Li can be explained by the desolvation of Li+ ions, as revealed by microcalorimetric studies. From this the coordination number of Li+ can be derived. The positive entropy leads to cooling of the electrode, which may influence lithium plating in lithium‐ion batteries.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>